Study of a Layered Plate Girder Element of Composite Materials and Its Applications - Yanqun Han; Li Chen; Wenqi Hou (Applied Sciences, 2023)
This study aims to provide an effective method to study the behavior of a steel–concrete composite deck. First, the structural characteristics of the composite deck and the challenges arising in the computational analysis of the structure using general software are described. Then, an LPGE element that combines the plate element and the girder element into one element to conveniently construct the model with high computation efficiency is proposed. Based on the principle of multivariate field function, the constraint matrix for the plate and girder and the stiffness matrix for the LPGE are derived. The LPGE method is used to study the behavior of the composite deck through the computation of a steel truss arch bridge. The computation results are compared with the results obtained in ANSYS and the test results to verify the correctness and effectiveness of the LPGE method. The results of the paper offer references for the analysis of steel–concrete composite decks.